2007
DOI: 10.1590/s0103-84782007000500050
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular markers on bovine chromosome 18 associated to calving interval in a Brangus-Ibagé cattle herd

Abstract: In the detection phase of a bovine marker assisted selection program, this paper investigated the genetic variability of three microsatellites on the chromosome 18 (BTA 18). The possible associations between genotypes or alleles of these markers versus weight at first calving and a lifetime calving interval (as indicators of reproductive performance) were evaluated in a beef cattle herd (5/8 Aberdeen Angus x 3/8 Nelore). Eleven alleles were detected in TGLA227 and ILSTS002 and three in BMS3004, the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
3
1
1
Order By: Relevance
“…In contrast to previous findings (ALMEIDA et al, 2003;DUARTE;OLIVEIRA et al, 2005;WEIMER et al, 2007), no association was found between reproductive performance and the BMS3004, BM4325, HEL05, AFZ1, and LEP Sau3/A1 markers. Therefore, these associations seem to be specific to the previous herds and might not be useful for MAS in other cattle breeds or herds.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous findings (ALMEIDA et al, 2003;DUARTE;OLIVEIRA et al, 2005;WEIMER et al, 2007), no association was found between reproductive performance and the BMS3004, BM4325, HEL05, AFZ1, and LEP Sau3/A1 markers. Therefore, these associations seem to be specific to the previous herds and might not be useful for MAS in other cattle breeds or herds.…”
Section: Discussioncontrasting
confidence: 99%
“…Another association detected was a significant higher frequency of ILSTS002 137 in cows with lower reproductive performance (Table 2). In a previous study, Weimer et al (2007) reported that animals carrying at least one ILSTS002 135 allele have on average, longer calving intervals over the reproductive lifetime. Several reasons may explain the difference between the previous findings by and the present study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Oliveira et al (2005) relatam associações entre genótipos favoráveis para os marcadores HEL5 e AFZ-1 associados ao gene do receptor para o IGF-1 (IGF-1R) e desempenho reprodutivo. Weimer et al (2007) No presente trabalho, buscou-se uma associação entre a taxa de natalidade em vacas de corte Aberdeen Angus e marcadores moleculares e polimorfismos em genes relacionados à reprodução, como IGF1-R, LHβ, Leptina, FSHR e LHR.…”
unclassified